Identifikasi dan Deteksi Aspergillus sp. Pembawa Gen Patulin pada Gaplek (Dried Cassava) dari Gudang Penyimpanan Gunung Kidul â Yogyakarta - , Sari Suhendriani; , Prof. Dr. Ir. Endang S. Rahayu MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Patulin is a sekunder metabolite, like several other major mycotoxins, such as, aflatoxins, fumonisins and ochratoxins. This mycotoxin may found in apples and apple-derived products, wheat flour, cereals, legumes, and bread. Exposure to this mycotoxin is associated with immunological, cancer, neurological and gastrointestinal outcomes. Patulin is produced by several species of mold, especially Aspergillus, Penicillium and Byssochlamys. Aspergillus is the dominant mold contaminate food commodities such as dried cassava in Indonesia. Aim of this research is to detect Aspergillus of dried cassava which potential gene carrier of patulin. Identification of mold was carried out based macroscopic and microscopic characters followed by confirmation based on molecular character using PCR protocols. To detect the patulin producer, isoepoxydon dehydrogenase (idh) gene of the patulin metabolic pathway was used. Result of this study showed that, 3 among 8 isolates representing Aspergillus spp were detected carrying the idh gene, indicated their potential in producing patulin. These isolate were identified as KP.A2.4a (Aspergillus wentii), KP.A1.5 (Aspergillus tamarii) and ST.B2.1a (Aspergillus tamarii). Whereas 5 isolates were not detected carrying idh genes.